Dichlorophosphanyl isocyanate – spectroscopy, conformation and molecular structure in the gas phase and the solid state. Issue 37 (12th September 2016) - Li, Dingqing; Schwabedissen, Jan; Stammler, Hans-Georg; Mitzel, Norbert W.; Willner, Helge; Zeng, Xiaoqing
Abstract : The conformation and structure of dichlorophosphanyl isocyanate, Cl2 PNCO, in both the gas phase and the solid state have been studied. Abstract : Dichlorophosphanyl isocyanate, Cl2 PNCO, was synthesized and characterized by IR, Raman and 31 P NMR spectroscopy. The conformational properties and molecular structures were studied by using gas electron diffraction (GED), X-ray crystallography and quantum-chemical calculations. Extensive DFT and ab initio calculations show that the potential energy surface of Cl2 PNCO upon rotating the P–N bond is rather flat; three conformers, namely syn, anti and gauche between the NCO group and the bisector of the ClPCl angle, were theoretically predicted. Experimentally, only one conformer was indicated by gas-phase IR spectroscopy and the preference for a gauche conformation in both gas phase and solid state was unambiguously ascertained by gas electron diffraction and X-ray crystallographic data. In the solid state, the Cl2 PNCO molecules adopt a gauche conformation with two distinct dihedral angles Cl–P–N–C of −121.3(2) and 137.4(2)° and form polymeric chains through weak intermolecular C⋯O contacts. Additionally, the dynamic character of the position of the isocyanate group of Cl2 PNCO was examined in the gas phase.